The Importance of Gamma‐Glutamyltransferase Activity in Patients with Coronary Artery Disease - Demircan, Sabri (Clin Cardiol, 2009)
BACKGROUND: In this study, we sought to investigate the relation of gamma‐glutamyltransferase (GGT) levels with the significance of coronary artery disease (CAD), clinical presentation, left ventricular (LV) function, and inflammatory activity. METHODS: A total of 235 patients (mean age: 60.1 ± 10.5 years, 166 [70%] males) who had coronary angiography were included in the study. Patients who had CAD constituted the study group (Group 1, n=189) and patients who had insignificant coronary disease or normal coronary activity constituted the control group (Group 2, n=46). RESULTS: GGT levels were higher in Group 1 than Group 2 (38.7 ± 30.9 U/L versus 27.5 ± 17.5 U/L, p =0.025). Left ventricular ejection fraction (LVEF) was lower in Group 1 than Group 2 (52.6% ± 11.7% versus 58.8% ± 11.3%, p < 0.002). GGT activity (40.2 ± 32.5 U/L versus 29.1 ± 18.3 U/L, p < 0.002) and c‐reactive protein (CRP) levels (33.9 ± 43.6 mg/dl versus 17.8 ± 29.8 mg/dl, p < 0.002) were higher, LVEF (52.6% ± 12.1% versus 56.5% ± 11.0%, p =0.021) was lower in patients with acute coronary syndrome compared with stable CAD group. In regression analysis, CRP levels (p < 0.0001, odds ratio [OR]=3.77, 95% confidence interval [CI] 0.10 < OR < 0.32), LVEF (p =0.016, OR=− 2.44, 95% CI − 0.95 < OR < − 0.10) and LV end‐diastolic pressure (p =0.015, OR=4.31, 95% CI − 1.19 < OR < − 0.13) were independent predictors of GGT activity. CONCLUSIONS: The increased GGT activity is related to LV function, clinical stability, and inflammatory activity rather than the severity of CAD. Measurement of GGT activity may be useful in predicting cardiovascular risk. Copyright © 2009 Wiley Periodicals, Inc.